2018
DOI: 10.1002/lol2.10064
|View full text |Cite
|
Sign up to set email alerts
|

Extreme isomeric complexity of dissolved organic matter found across aquatic environments

Abstract: The natural aquatic environment contains an enormous pool of dissolved reduced carbon, present as ultracomplex mixtures that are constituted by an unknown number of compounds at vanishingly small concentrations. We attempted to separate individual structural isomers from several samples using online reversedphase chromatography with selected ion monitoring/tandem mass spectrometry, but found that isomeric complexity still presented a boundary to investigation even after chromatographic simplification of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 44 publications
8
128
0
2
Order By: Relevance
“…In the following, we use the term chromatographic feature to mean a nonresolved peak, and reserve the word peak for true analyte peaks (which are rare in DOM) or resolved mass spectrometry peaks, which usually contain information from numerous isomers with the same formula. 9,13 The use of the term elution profile or chromatographic feature of components or formulas does not imply single analyte peaks, but always refers to complex mixtures unless specifically stated otherwise. All data processing and modelling was carried out using PLS_Toolbox (v8.61, Eigenvector Research Inc.) in MATLAB (v9.7, MathWorks Inc.).…”
Section: Chemometric Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In the following, we use the term chromatographic feature to mean a nonresolved peak, and reserve the word peak for true analyte peaks (which are rare in DOM) or resolved mass spectrometry peaks, which usually contain information from numerous isomers with the same formula. 9,13 The use of the term elution profile or chromatographic feature of components or formulas does not imply single analyte peaks, but always refers to complex mixtures unless specifically stated otherwise. All data processing and modelling was carried out using PLS_Toolbox (v8.61, Eigenvector Research Inc.) in MATLAB (v9.7, MathWorks Inc.).…”
Section: Chemometric Analysismentioning
confidence: 99%
“…From the molecular perspective, the dominant molecular formulas were usually present in several components (Fig. S12 †), highlighting the isomeric diversity hidden behind each formula, 13,32 and revealing for the first time that isomers can be grouped by behaviour across environments.…”
Section: Component Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no direct measurement was conducted, a recent study suggested that riverine DOM after storm events could potentially have high structural diversity (Wagner et al, 2019), based on modeling results (Zark et al, 2017;Hawkes et al, 2018;Zark and Dittmar, 2018). Based on the central limit theorem, these modeling studies assumed a random combination of atoms in DOM molecules and suggested that each formula assigned in ultrahigh-resolution mass spectrometry potentially represents 10-100 different isomers (Zark et al, 2017;Hawkes et al, 2018). Our results, however, suggested an opposite pattern.…”
Section: Changes In the Geometric Configuration And Isomeric Compositmentioning
confidence: 99%